The effect of modulating ATP-sensitive potassium channels in frog skeletal muscle, in vitro, during fatigue and metabolic inhibition. - Gramolini, Anthony Orlando. (University of Ottawa (Canada), 1996)
The ATP-sensitive potassium (K$\sp+\rm\sb{(ATP)}$) channel is a K$\sp+$ channel which is activated as the energy state of a muscle decreases. It has been hypothesized that once activated, K$\sp+\rm\sb{(ATP)}$ channels decrease the excitability of the cell and cause decreased contractility, such as during fatigue, in order to prevent energy levels from falling to dangerously low levels. The purpose of this study was to test this hypothesis and to determine under which conditions K$\sp+\rm\sb{(ATP)}$ channels can contribute to a decrease in force during a metabolic stress in the sartorius muscle of the frog, Rana pipiens. In the first series of experiments, sartorius muscle fibres were fatigued with 100 msec long tetanic contractions every second for three minutes, a condition known to activate ATP-sensitive potassium channels. So if K$\sp+\rm\sb{(ATP)}$ channels contribute to a decrease in force during fatigue, an activation of K$\sp+\rm\sb{(ATP)}$ channels with channel openers should further decrease membrane excitability and contractility. In a second series of experiments, muscles were subjected to metabolic inhibition which is known to activate a large number of K$\sp+\rm\sb{(ATP)}$ channels in order to better understand the relationship between K$\sp+\rm\sb{(ATP)}$ channel activity, the bioenergetic state, and force. The goal was to determine if K$\sp+\rm\sb{(ATP)}$ channels can contribute to a decrease in force under a bioenergetic state that is within physiological limits. (Abstract shortened by UMI.)
Keywords: Biology, Animal Physiology.